2005
DOI: 10.4140/tcp.n.2005.514
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Neuropsychiatric Pharmacists in a Memory Disorder Clinic

Abstract: Pharmacists have valuable skills to assist in the management of diagnosis and management of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Patients referred to specialist aged care and memory disorder clinics are likely to be at high risk for MRPs due to factors such as polypharmacy and cognitive dysfunction [5–11]. Although they are not usually referred primarily for a comprehensive medication review, this might be an opportune time to conduct such a review [12]. Several studies have demonstrated clinical and cost benefits associated with clinical pharmacy services in outpatient clinics for older people [13–18], but there has been no Australian study conducted in the aged care outpatient setting and no study internationally conducted in a memory disorder clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Patients referred to specialist aged care and memory disorder clinics are likely to be at high risk for MRPs due to factors such as polypharmacy and cognitive dysfunction [5–11]. Although they are not usually referred primarily for a comprehensive medication review, this might be an opportune time to conduct such a review [12]. Several studies have demonstrated clinical and cost benefits associated with clinical pharmacy services in outpatient clinics for older people [13–18], but there has been no Australian study conducted in the aged care outpatient setting and no study internationally conducted in a memory disorder clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Another example exists in patients being treated for other neurological disorders such as Parkinson’s disease, multiple sclerosis, or cerebrovascular disease, in which pharmacists can assist in recommending and monitoring effectiveness of treatment choices. 18…”
Section: Clinic Modelsmentioning
confidence: 99%
“…1-4 Conversely, there is a paucity of literature describing the role of a pharmacist in interdisciplinary memory clinics, and less is known of a pharmacist practicing in interdisciplinary, primary care–based memory clinics. 5-7 It is important to disseminate the pharmacist’s role in new clinic models in appropriate detail to guide others on how to address challenges or to assist in the development of similar models. The purpose of this article is to describe how clinical pharmacists provide collaborative care to patients presenting with cognitive concerns in a primary care–based, interdisciplinary memory clinic.…”
Section: Introductionmentioning
confidence: 99%